A methods engineering study on Miracle Candles Cottage Industries - Aquino, Diana Sylvia; Cruz, Jennifer D.; Limpiada, Diane Marie Madel; Nachura, Aaron Cirilo (Diliman, Quezon City College of Engineering, 2003)
Knowing the essential components of a manufacturing firm, namely the operating procedure and processes in the direct manufacturing of the products and documents flow, the overall performance of the company is highly depended in the efficiency and effectiveness of the said components. The study conducted in Miracle Candles Cottage Industries, a medium scale candle manufacturing firm, was concentrated on finding improvements that could be implemented to these components to further fulfill their purpose. The improvements were mainly aiming to increase productivity and to reduce cost. In the different processes involved in the study, a task is to be fulfilled. These tasks are data gathering which includes documentation, problem identification and verification, generation of alternatives, implementation and standardization. In fulfilling these tasks, different problem solving tools with respective functions are to be used with appropriation. The problems identified in the company were more on the inefficiencies related to the manual procedures consequently appropriate recommendations were generated to address these problems. Among the problems identified are the prolonged productions in the wick-first and dipped candles which were identified to be caused by weak ergonomic designs, methods problems and layout deficiencies. Motion study and tool design analysis was conducted to address the problems regarding manual work done. With this motion study, improvements in the work stations (dipping and wick first section) and facility layout which include the relocation of the different work areas were carried out to reduce transport distance, production time, worker's fatigue rate and discomfort. Aside from the problems in the manual work, problems were also identified in relation with the company's nature and structure. Miracle Candles Cottage Industry is a partnership among biological related people with their workers composed of their other relatives, thus the implementation of systems, procedures and policies were overlooked to a certain extent. Specific manifestations of these as identified were unclear job distribution among the managers that only one of them performs the bulk of the job. Another is the improper behavior of the workers (unmotivated and lax workers) being the relatives of the owners. To address these problems, establishing a more organized hierarchy of the management was done. This is to clarify the job description and allocation among the members of the management. In the problem which involved the low workers motivation and improper behavior, a more appropriate wage and incentive plans and other wage and incentive related rules were proposed to address the problem. In the generation of alternatives for the different problems, evaluations of the alternatives are done to determine the most effective in addressing the specified problem. Upon identifying the best alternative, implementation plans and strategies were developed. In production aspect, the proposed designs and layouts were quite minor which only required a relatively small amount of funds and time to be able to proceed with the implementation. In the systems and procedures part, the implementation requires revisions in the company's policies and management's structure. After the implementation, it is projected that an increase in productivity will be attained. This increase in productivity is quantified in terms of the reduced cycle times and distances traveled in going on with the methods of productions holding the inputs and outputs constant. After the management-related improvements were implemented, it could be expected that the company would utilize its resources (raw materials and manpower) better resulting to savings and better working relationships among the workers and the management. In carrying out the whole study, the techniques in methods engineering are extensively used. The determination of the most appropriate approach in identifying as well as solving problems was mandatory to effectively perform the tasks.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering